Factors Affecting Prognosis in Patients with Extramedullary Myeloma: A Single-Center Experience - Ersin Bozan; Samet Yaman; Gökcen Bozan; Mahmut Esad Durmuş; Burcu Aslan Candır; Uğur Hatipoğlu; Barış Boral; Dicle İskender; Bahar Uncu Ulu; Tuğçe Nur Yiğenoğlu; Mehmet Sinan Dal; Fevzi Altuntaş (Journal of Clinical Medicine, 2026)
Background/Objectives: In multiple myeloma, extramedullary involvement confers poor prognosis. Extramedullary involvement in multiple myeloma may manifest at the time of diagnosis or during a relapse, and it represents a severe condition. Patients with bone involvement are referred to as EM-B, while those with soft tissue involvement are referred to as EM-S. Although various studies have been conducted, the number of studies that categorize extramedullary involvement and examine the effects of flow cytometry, treatment, and genetic findings on prognosis is quite limited. We aimed to contribute to the literature by addressing this gap. Methods: In our study, we retrospectively examined the data of 281 patients followed at our center between 2011 and 2023. Clinical/laboratory data and flow cytometry profiles were collected. Survival was analyzed using Kaplan–Meier and Cox models; logistic regression was used for categorical variables. Hazard ratios (HRs), odds ratios (ORs), and 95% confidence intervals (CIs) were calculated; p-values were reported to three decimals. Results: Extramedullary involvement was absent in 134 (47.7%) patients, while involvement was detected in 147 (52.3%) patients. The median age of the patients was 60 years, and the median follow-up period was 35.4 months. No association was found between CD56 expression on plasma cells, higher Revised Multiple Myeloma International Staging System (R-ISS) score, and extramedullary involvement. Overall survival (OS) was found to be significantly lower in patients with extramedullary involvement. Conclusions: The findings of our study are consistent with many studies in the literature, supporting the finding that survival rates are lower in myeloma patients with extramedullary involvement. Further studies are needed to elucidate the pathogenesis in patients with extramedullary involvement in multiple myeloma and to provide a basis for targeted therapies. Studies involving immunotherapy and cellular therapies may offer a new avenue for these patients.